Clinical manifestations of Herpes simplex in children. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2019)
The clinical manifestations of herpes simplex in children are reviewed. The first contact with the virus occurs early, often in the first year of life, even though in the developed countries this first contact is moving towards a more advanced age. In most cases the primary infection is clinically not very evident or presents non-specific clinical manifestations that do not allow to recognize it. Primary infection is clinically recognizable when specific mucocutaneous lesions are present; it is a severe disease that can be fatal especially in the neonatal period when in most cases the infection is contracted during the passage through the birth canal. Among the other primary infections with cutaneous involvement there are herpetic gingivostomatitis, primary herpetic eruption on previous dermatitis and zosteriform Herpes simplex. After the primary infection the virus goes into a sensory nerve ganglion where it remains for a lifetime in a state of latency, during which it cannot be attacked by the various antiviral remedies. Numerous factors can reactivate the virus that starts to multiply rapidly and moves from the nerve ganglion to the skin where it is responsible for localized recurrent infections always in the same site.